Pengaruh Rasio Keuangan, Kompleksitas, dan Kualitas Audit terhadap Audit Delay pada Perusahaan Manufaktur di BEI - Ary Apriliana Dewi; Made Arie Wahyuni (Universitas Pendidikan Ganesha, 2021)
This research aims to determine the effect of financial ratios, company complexity and audit quality on audit delay in manufacturing companies listed on the Indonesia Stock Exchange. The type of research is quantitative research. This research uses secondary data from the Indonesia Stock Exchange. The population in this research are manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019 totaling 178 companies. The sampling technique used purposive technique. The sample obtained was 74 companies with observations for three years the total observations were 222. The analytical method used was descriptive analysis, classical assumption test, and multiple regression test. The results of this research are (1) profitability has a negative effect on audit delay, (2) solvency has a positive effect on audit delay, (3) company complexity has a positive effect on audit delay, (4) audit quality has a positive effect on audit delay in manufacturing companies that listed on the IDX in 2017-2019.Keywords: Profitability, Solvency, Company Complexity, Audit Quality, Audit Delay